2013
DOI: 10.1016/j.ijgo.2013.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a single preoperative dose of sublingual misoprostol on intraoperative blood loss during total abdominal hysterectomy

Abstract: The results showed that a single dose of misoprostol administered before abdominal hysterectomy resulted in a significant reduction of blood loss with minimal adverse effects. Clinical Trial Registry India (www.ctri.nic.in): CTRI/2011/091/000216.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 18 publications
(33 reference statements)
5
6
0
Order By: Relevance
“…Another study also supports our results by Biswas et al [14] , in which 132 patients undergoing total abdominal hysterectomy with or without bilateral salpingo-oophorectomy for symptomatic myomas were randomly allocated to receive either 400 μg of sublingual misoprostol or placebo 30 minutes before surgery. The average blood loss was significantly higher in the placebo group (435 ml) versus misoprostol group (356ml).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Another study also supports our results by Biswas et al [14] , in which 132 patients undergoing total abdominal hysterectomy with or without bilateral salpingo-oophorectomy for symptomatic myomas were randomly allocated to receive either 400 μg of sublingual misoprostol or placebo 30 minutes before surgery. The average blood loss was significantly higher in the placebo group (435 ml) versus misoprostol group (356ml).…”
Section: Discussionsupporting
confidence: 88%
“…In the study by Kalogiannidis et al [11] , the rate of side effects was similar between groups, which agree also with the studies by Shokeir et al [13] and Biswas et al [14] .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…who tested the effect of using sublingual 400 μg misoprostol taken 30 min pre‐operatively in 32 women undergoing total abdominal hysterectomy (TAH) versus 32 women receiving placebo with no observed difference in intra‐operative blood loss. However, Biswas et al . showed that single dose of sublingual 400 μg misoprostol 30 min before (TAH) resulted in a significant reduction of intra‐operative blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…A similar conclusion was obtained by Chaiet et al (20) who tested the effect of using sublingual 400 μg misoprostol taken 30 min pre-operatively in 32 women undergoing total abdominal hysterectomy (TAH) versus 32 women receiving placebo with no observed difference in intra-operative blood loss. However, Biswas et al (21) showed that single dose of sublingual 400 μg misoprostol 30 min before (TAH) resulted in a significant reduction of intra-operative blood loss.…”
Section: Kongnyuy and Wiysongementioning
confidence: 99%